HEPATITIS B ORTHOHEPADNAVIRUS AND CORONOVIRUS INTERFERENCE - Absamat Abdurakhimovich Oslanov; Jonibek Fayzullaevich Kadirov; Saidolim Murodkosimov; Nodir Nuriddinovich Kobilov (Scholar Express Journals, 2022)
The purpose of this study is to direct the study of patients with chronic hepatitis C virus in 2020-2021. with a low incidence of COVID - 19 and the fact that the disease is transmitted mildly in patients with hepatitis C virus or their components may have had an inhibitory effect on coronavirus replication Researchers compared 105 patients who were under dispensary control with chronic viral hepatitis B with COVID 19 cases during the COVID-19 pandemic (2020-2021 ), 115 patients treated with COVID 19 in specialty hospitals during the pandemic, with their medical records. The authors reported that COVID-19 was rare among people with chronic viral hepatitis B and that people with COVID-19 had the disease as a mild degree of coronavirus acute respiratory illness
Keywords: Chronic Viral Hepatitis B COVID 19; Coronoviruses; Viruses Interference